Lembaga Lokal sebagai Strategi Pemberdayaan Masyarakat Pedesaan (Kasus Arisan Terop di Kecamatan Kesamben Kabupaten Jombang Propinsi Jawa Timur. Local Institution as the Strategy of Empowering Rural Communities (The Case - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThe object of this research is to explain a lettery as the strategy of empowering local communities at Kesamben Subdistrict, Jombang Regency, East Java. The objective of this research is to find out aspects that stimulating the establishment of the needed lettery either simultanously, directly or indirectly.The result of the research shows that there are four matters influencing the running of the local institutions optimally : (1) Wholly eliminating luxurious behaviour, (2) nerm system, (3) personnel support, and (4) facility support. The luxurious behaviour makes the communities indebted and powerless. The norm system is actually intended to help the communities free from debt at the beginning but it has been developed along with the development of the personnel support. The facility support is also very important to keep the arisan terop existing.The running of the four matters which are simultaneous and related among them is the form of empowering the communities.